2021
DOI: 10.1186/s13017-021-00348-1
|View full text |Cite
|
Sign up to set email alerts
|

If laparoscopic technique can be used for treatment of acutely incarcerated/strangulated inguinal hernia?

Abstract: Purpose Laparoscopic treatment for acutely incarcerated/strangulated inguinal hernias is uncommon and controversial. In the present study, we assessed the safety and feasibility of transabdominal preperitoneal (TAPP) repair for the treatment of acutely incarcerated/strangulated inguinal hernias. Methods Patients with acutely incarcerated/strangulated inguinal hernias who underwent TAPP repair at the Department of Hernia and Abdominal Wall Surgery (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The laparoscopic approach was reported to result in reduced morbidity in Bochdalek DH and might facilitate hernia reduction, haemostasis, and adhesiolysis [13]. Moreover, some reports described the feasibility of laparoscopy in similar conditions, such as in strangulated inguinal hernia and strangulated small bowel obstruction [14,15]. Minimally invasive surgery can be indicated for older adult patients with liver dysfunction and iatrogenic complications, such as in this case.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The laparoscopic approach was reported to result in reduced morbidity in Bochdalek DH and might facilitate hernia reduction, haemostasis, and adhesiolysis [13]. Moreover, some reports described the feasibility of laparoscopy in similar conditions, such as in strangulated inguinal hernia and strangulated small bowel obstruction [14,15]. Minimally invasive surgery can be indicated for older adult patients with liver dysfunction and iatrogenic complications, such as in this case.…”
Section: Discussionmentioning
confidence: 78%
“…Pneumothorax is a potential complication of laparoscopic hernia defect repair, and other potential complications include bowel injury during the reduction and handling of the intruded intestine [13]. Blind, forceful traction is discouraged [14]. If irreversible ischaemic changes of the intruded intestine are extensive and the intestine is fragile, laparoscopic hernia reduction can be challenging and dangerous [15].…”
Section: Discussionmentioning
confidence: 99%
“…Trans -abdominal pre-peritoneal has become an acceptable approach in the management of inguinal hernia in acute setting, either obstruction or incarceration [4] . It allows inspection of the contents during spontaneous reduction as often occurs following anesthesia, negating a formal laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The search string in free text search contained the following keywords: ("INGUINAL HERNIA" OR "GROIN HERNIA OR "FEMORAL HERNIA") AND "EMERGENCY". Surprisingly we found only four original articles who cite this condition and the evolution of these [4][5][6][7] . However, none of them had the contralateral hernia approach as a study objective, therefore lacking data from this specific population.…”
Section: Textmentioning
confidence: 97%
“…In 2013, the European Association for Endoscopic Surgery concluded that TAPP can be an option for treatment of incarcerated inguinal hernias 3 . Liu et al analized 94 patients who underwent TAPP for treatment of inguinal hernia in the emergency and found unrecognized contralateral hernia in 15 patients (15.9%) 4 . Mancini et al 5 reported an incidence of intraoperative diagnosis of contralateral hernia in 4 out 20 (20%) patients who underwent TAPP for hernia repair in the emergency.…”
Section: Textmentioning
confidence: 99%